KEWENANGAN CAMAT DALAM PENYELENGGARAAN PEMERINTAHAN DESA DI KECAMATAN TAPUNG KABUPATEN KAMPAR TAHUN 2016 - Alhamri, Ade; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
District is part of the district / municipality government in carrying out its duty to obtain the delegation of some authority of Regent / Mayor for the portion of regional autonomy. Governmental science is an applied science because it prioritizes the aspect of use in practice, namely in the relationship between the former (people) (the Hamasaki, Citizenship Education). This research was conducted in subdistrict Tapung Kampar District, with problem formulation, Why is the Authority of Camat in Implementation of Village Governance and Supervision Not Optimal?. To know and explain the authority of sub-district head in the administration of village administration in Tapung Sub-district, Kampar Regency in 2016 and to know the factors of not yet optimal authority of sub-district administrator in the village administration in Tapung District Kampar regency. This research uses descriptive explanatory method using Qualitative research design. Primary data types: data on security factors and data on authority constraints, informants in this study are Camat, Camat Secretary, Head of Village Government Affairs, Village Deliberation Agency, Village Head, Village Secretary. Technique of completion of this research data use Interview, Observation, Documentation, and Literature Study. So this result of this research: Camat in coaching in fostering governance is enough role in its implementation. The obstacles to village governance in the tapung dap kampar are the low level of education and the thought of the village administration in the management and maintenance of the village so that it is difficult to improve the quality of the existing human resources management and management of the village, so what are their duties and responsibilities abandoned, village officials are also less budget in the implementation of coaching. Keywords: Regional autonomy, authority, Coaching, Village Governance